Use of platelet-rich fibrin in fat grafts during facial lipostructure - Zhang, Zhaoxiang; Qiu, Lihong; Cui, Dong; Geng, Jian; Yi, Chenggang (Frontiers in Surgery, 2022)
Background: This review was designed to discuss the safety and efficacy of using platelet-rich fibrin (PRF) in fat grafts during facial lipostructure. Methods: From January 2018 to December 2021, 650 fat grafts for facial lipostructure were performed in the authors’ department. According to their wishes, we divided the patients into two groups: 498 patients were treated with autologous fat injection (control group), and 152 patients were treated with autologous fat injection combined with PRF. All of the patients were monitored for at least six months. The effects were evaluated via physician assessment and patient satisfaction rates, and the incidences of complications were compared. Results: All the cases had a degree of improvement after treatment. The patient satisfaction rate was 55.3% in the PRF group and 43.4% in the control group. In all, 68.4% of the patients in the PRF group and 58.2% in the control group indicated that one-stage surgery was sufficient to achieve the desired effect. According to the evaluation conducted by the plastic surgeon, 59.2% of patients in the PRF group and 47.0% in the control group achieved a perfect effect. A total of 76.3% of patients in the PRF group and 63.9% in the control group reported that one surgery achieved satisfactory results. The difference between the PRF and control groups was statistically significant. Conclusion: Using an autologous fat graft during facial lipostructure is beneficial and safe when combined with PRF. The combination may enhance the effect and satisfaction rate. Further research and prospective clinical studies are needed to understand the role of PRF in fat grafting.